Does oral glutamine improve insulin sensitivity in adolescents with type 1 diabetes? - Torres-Santiago, Lournaris (Nutrition, 2016)
OBJECTIVE: The decline in insulin sensitivity (S(I)) associated with puberty increases the difficulty of achieving glycemic control in adolescents with type 1 diabetes (T1D). The aim of this study was to determine whether glutamine supplementation affects blood glucose by enhancing S(I) in adolescents with T1D. METHODS: Thirteen adolescents with T1D (HbA1C 8.2 ± 0.1%) were admitted to perform afternoon exercise (four 15-min treadmill/5-min rest cycles of exercise) on two occasions within a 4-wk period. They were randomized to receive a drink containing either glutamine (0.25 g/kg) or placebo before exercise, at bedtime, and early morning in a double-blind, crossover design. Blood glucose was monitored overnight, and a hyperinsulinemic-euglycemic clamp was performed the following morning. RESULTS: Blood glucose concentration dropped comparably during exercise on both days. However, the total number of nocturnal hypoglycemic events (17 versus 7, P = 0.045) and the cumulative probability of overnight hypoglycemia (50% versus 33%, P = 0.02) were higher on the glutamine day than on the placebo day. During clamp, glucose infusion rate was not affected by glutamine supplementation (7.7 ± 1 mg • kg(−1) • min(−1) versus 7.0 ± 1; glutamine versus placebo; P = 0.4). CONCLUSIONS: Oral glutamine supplementation decreases blood glucose in adolescents with T1D after exercise. Insulin sensitivity, however, was unaltered during the euglycemic clamp. Although the mechanisms involved remain to be elucidated, studies to explore the potential use of glutamine to improve blood glucose control are needed.